2021
DOI: 10.2147/idr.s326230
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phage Therapy for Pulmonary Infection of Mouse by Liquid Aerosol-Exposure Pseudomonas aeruginosa

Abstract: Background: Pseudomonas aeruginosa is an important nosocomial infectious bacterium, more and more multidrug resistant P. aeruginosa have been isolated and posed severe challenges to clinical antibiotic treatment, bringing additional morbidity, mortality, and economic burden. Bacteriophages can lyse bacteria specificity and are feasible alternatives to antibiotics. Methods: A Pseudomonas aeruginosa-infecting phage vB_PaeP_PA01EW was isolated. Phage plaque assays, transmission electron microscopy, host-range det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
5
8
0
Order By: Relevance
“…In contrast, Podoviridae seem to be more affected by the 45 °C temperature. These data agreed with [ 44 ], who found the same viability loss after a 15 min exposition at 50 °C (−1 log PFU) and at 60 °C (−2 logPFU/mL). In conclusion, it is unlikely that viability loss by tail breakage of Myoviridae would be due to high temperature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, Podoviridae seem to be more affected by the 45 °C temperature. These data agreed with [ 44 ], who found the same viability loss after a 15 min exposition at 50 °C (−1 log PFU) and at 60 °C (−2 logPFU/mL). In conclusion, it is unlikely that viability loss by tail breakage of Myoviridae would be due to high temperature.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that these parameters have no significant impact on phage viability, whatever the phage family ( Figure 5 c). This result was also described by Zhang et al (2021) for a 37 °C biological temperature [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The therapeutic potential of bacteriophages targeting MDR strains of GNB using animal models was evaluated in vitro and showed high infectivity of phages and multiple phage doses were required for effective treatment in vivo [ 113 ]. Novel treatment options such as PlyF307 lysine phage against MDR A. baumannii , VTCCBPA43 phage against virulent K. pneumoniae , PlyPa91 and vB_PaeP_PA01EW phages against P. aeruginosa , and Abp95 lytic myoviridae phage against multi-genotypes of carbapenem-resistant A. baumannii were demonstrated in mouse models [ 114 118 ]. Tridecaptins, a non-ribosomal lipopeptide, showed a selective bactericidal activity against the gram-negative version of the peptidoglycan precursor lipid II on the outer leaflet of the inner membrane and disrupts the proton-motive force [ 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hua et al (2017) and Kvachadze et al (2011) reported that in clinical trials, no side effects were observed during the treatment of pulmonary infections by bacteriophage nebulization [ 34 , 35 ]. Yajun et al (2021) evaluated phage therapy for a lung infection in mice by liquid aerosol-exposure Pseudomonas aeruginosa [ 36 ]. The authors reported no obvious alterations in the lung tissue of the phage group in comparison to the control group.…”
Section: Resultsmentioning
confidence: 99%